THE ROLE OF THE QUR’AN MEMORIZATION (TAHFIDZ) PROGRAM IN SHAPING THE CHARACTER OF STUDENTS’ SOCIAL PIETY AT MTS SWASTA DARUL ULUM BUDI AGUNG MEDAN - Sakinah; Makmur Syukri (SOSIOEDUKASI, 2026)
This descriptive qualitative research aims to analyze the role of the Al-Qur’an memorization program in shaping the social piety of students at the Darul Ulum Budi Agung Medan Private Islamic Junior High School. This research is motivated by the rise of juvenile delinquency, such as lack of manners, declining social awareness, and individualistic attitudes, so that the strengthening of real religious education in everyday life is needed. Data were collected through observation techniques, in-depth interviews, and documentation. The memorization program at this madrasah developed from an extracurricular activity to a subject and then formed a special class, by applying the muraja’ah, sabaq, and mutaba’ah methods. The results of the study show that the character of social piety of students has increased significantly through this program. The memorization program has proven to be a major driver of student behavioral transformation that has a direct impact on three aspects: shaping students’ speech to be softer, increasing respect and politeness towards parents, and building a consistent awareness of worship.